Social networking site use in young adolescents: association with health-related quality of life and behavioural difficulties - Jenkins,R; Shen,C; Dumontheil,I; Thomas,MSC; Elliott,P; Roosli,M; Toledano,M (Computers in Human Behavior, 2020)
Despite Social Networking Sites (SNS) having a minimum age of 13, younger adolescents are using them. In this study, we examine self-reported overall SNS use and SNS use if awake at night in relation to Health-Related Quality of Life (HRQOL, measured by KIDSCREEN-10) and behaviour (measured by Strengths and DifficultiesQuestionnaire, SDQ) in 5229 adolescents aged 11–12 in the Study of Cognition, Adolescents and Mobile Phones (SCAMP) cohort. Two-thirds of the study population used SNS. Weekday and weekend SNS use on mobile phones and other devices was significantly associated with lower HRQOL in females (all p-values for linear trend < 0.01) but not males. Using SNS if awake at night was also significantly associated with lower HRQOL in females (adjustedβ-coefficient - 2.20 (95% CI - 3.18, - 1.22)). Higher SNS use on mobile phones and other devices was associated with increased behavioural difficulties in both genders (p-value for trend < 0.001). Similarly, SNS useif awake at night was associated with greater behavioural difficulties (adjusted β-coefficient 2.54 (95% CI 2.09, 2.98)). We recommend further longitudinal research in this area in order have a better understanding of the direction of relationships between SNS and wellbeing and behaviour in adolescents.